(untitled) (International Journal of Environmental Sciences, 2025)
The demand for eating ready-to-eat (RTE) vegetables in restaurants are increased, which is one of the reasons for maintaining a healthy lifestyle. This study aimed to assess the microbiological quality of RTE salads and handling practices during working in restaurants such as; Total count bacteria (TCB), coliform bacteria, Staphylococcus aureus, Salmonella sp., and fungi. Total of RTE salad samples (e.g. tomato, cucumber, lettuce, purple cabbage, white cabbage, Sellery, and mixed salad) and swab samples from utensil and place of working with RTE salads were collected from some local restaurants in central of Erbil. The samples were microbiologically analyzed. TCB ranged from 1.33 to 5.93 Log10CFU/g, which the highest TCB growth found in cucumber. The highest number of coliform bacteria was found in the lettuce samples. While, the highest growth of Staphylococcus aureus was found in sellery samples. Salmonella sp. found in two samples of tomato and three samples of sellery. Also, the results show that the growth ofmold and yeast ranged from 0.74 to 3.25 Log10CFU/g, according to the Iraq standard specifications for foods, some of the samples are unacceptable from the standpoint of microbiological safety; therefore, these data indicate that food handlers may contribute to pathogens contamination and that there are some handling practices that require more attention. The results of this study revealed that the high contaminations of these foods may be a potential hazard for public health.